Effect of Acupressure on Blood Glucose Level in Diabetes Mellitus Patients: Meta-Analysis - Muslihatin Khuril Rosyida; Didik Tamtomo; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from abnormalities in insulin secretion that affect blood sugar levels. Chronic hyperglycemia in DM is associated with long-term damage to several organs of the body. One of the interventions that can be given to lower blood sugar levels is acupressure therapy. The purpose of this study was to determine the effect of acupressure therapy on blood sugar levels in patients with diabetes mellitus.Subjects and Method: This study is a systematic review and meta-analysis with PICO, P: Diabetes mellitus patients, I: Acupressure, C: No acupressure, O: Blood sugar levels. The process of searching for articles is done through a database of journals including: Pubmed, Google Scholar, Science Direct, Scopus, Spinger Link, CNKI and Hindawi. The keywords used in the literature search were: “acupressure” AND “diabetes” AND “blood sugar” AND “blood glucose” AND “standard controlled trial”, “acupressure for diabetes”, “diabetes standardized controlled trial”, “acupressure randomized controlled trial”. trial”, diabetes acupoint, “diabetes and placebo”, “acupressure” AND “diabetes”. The articles included in the study were full text articles with a randomized controlled trial study design and the results were reported with the effect size, mean standard deviations (SMD). Articles were collected using PRISMA flow diagrams and analyzed using the Review Manager 5.3 application.Results: A meta-analysis of 9 articles reviewed in this study came from Taiwan, China, Indonesia, Egypt and Iran with a sample size of 451. The study results showed that acupressure therapy was able to reduce blood sugar levels in diabetes mellitus patients with SMD blood sugar values. acupressure was 0.56 units lower than no acupressure and was statistically significant with a significance value of (SMD=-0.56; 95% CI= -0.76 to -0.37; p<0.001).Conclusion: Acupressure therapy has the effect of lowering blood sugar levels in diabetes mellitus patients.Keywords: acupressure, blood sugar, diabetes mellitus.Correspondence: Muslihatin Khuril Rosyida. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: khurilrosyida@gmail.com. Mobile: 08564713149.Indonesian Journal of Medicine (2023), 08(01): 68-78https://doi.org/10.26911/theijmed.2023.08.01.07